2019
DOI: 10.1248/bpb.b19-00196
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Suppresses the Proliferation and Migration of Ox-LDL-VSMCs in Atherosclerosis through Upregulating miR-126-5p

Abstract: Atherosclerosis (AS) is a chronic inflammatory disease threatening human health, and vascular smooth muscle cells (VSMCs) are involved in AS processes. Baicalin is a flavonoid compound, which has antiatherosclerotic effect. The aim of our study was to explore the molecular mechanism of baicalin on AS. The expression of miR-126-5p was measured in peripheral blood of AS patients and healthy control. We found miR-126-5p expression was decreased in AS. Then, high-mobility group box 1 (HMGB1) was verified as a targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 34 publications
(35 reference statements)
2
31
0
Order By: Relevance
“…In addition, HMGB1 inhibition may be a potential therapeutic strategy for atherosclerosis ( 34 ). In the present study, the mRNA and protein levels of HMGB1 were measured, and the results demonstrated that the expression levels of HMGB1 were upregulated in ox-LDL-induced VSMCs compared with those in untreated cells, which was in line with a previous study ( 35 ). In addition, HMGB1 was demonstrated to be negatively regulated by miR-370-3p in the present study, and circ_0010283 upregulated HMGB1 expression via miR-370-3p.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, HMGB1 inhibition may be a potential therapeutic strategy for atherosclerosis ( 34 ). In the present study, the mRNA and protein levels of HMGB1 were measured, and the results demonstrated that the expression levels of HMGB1 were upregulated in ox-LDL-induced VSMCs compared with those in untreated cells, which was in line with a previous study ( 35 ). In addition, HMGB1 was demonstrated to be negatively regulated by miR-370-3p in the present study, and circ_0010283 upregulated HMGB1 expression via miR-370-3p.…”
Section: Discussionsupporting
confidence: 92%
“…Similar regulatory patterns were also found in other studies. An investigation conducted in atherosclerosis revealed that BAI inhibited the proliferation and migration of oxidized low‐density lipoprotein treated vascular smooth muscle cells by elevating the expression of miR‐126‐5p (Chen et al, ). Additionally, Dai et al figured out that BAI exerted its protective roles against high glucose‐evoked injuries through elevating miR‐145 expression in human pigment epithelial cells (Dai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the LDL-C, the miR-221/222 family was also associated with low HDL-C phenotype [15]. Similar to the association of miR-221/222 family with dyslipidemia (LDL-C/HDL-C), this phenomenon was also seen on miR-126-5p [16,17]. In addition, miR-490-3p [18], miR-320b [19], miR-210-3p [20], miR-17-3p [21] and miR-33a-5p [22] were linked to LDL-C metabolism while miR-22-3p [23], miR-31-5p [24], miR-378b [25], and miR-135a-3p [26] were linked to HDL-C metabolism.…”
Section: Discussionmentioning
confidence: 56%